Sex-specific associations of TCF7L2 variants with fasting glucose, type 2 diabetes and coronary heart disease among Turkish adults - Ayşe Berna Yüzbaşıoğulları; Evrim Kömürcü-bayrak; Altan Onat; Gunay Can; Nina Mononen; Reijo Laaksonen; Mika Kähönen; Terho Lehtimäki; Nihan Erginel-ünaltuna (Anatolian Journal of Cardiology, 2020)
Objective: TCF7L2 is a repressor and transactivator of genes, and its variants are strongly associated with diabetes. This study aimed to evaluate the sex-specific relationship between the most common TCF7L2 gene variants (-98368G>T, rs12255372 and -47833C>T, rs7903146) with diabetes and coronary heart disease in Turkish Adult Risk Factor (TARF) Study. Methods: Single nucleotide variants (SNVs) have been genotyped using the TaqMan allelic discrimination assays in 2,024 (51.3% in women, age: 55+-11.8) Turkish adults participating in the TARF study. Statistical analyses were used to investigate the association of genotypes with clinical and biochemical measurements. Results: Among the TARF study participants, 11.7%, 24.3%, 14.1%, and 38.3% had diabetes, hypertension, coronary heart disease (CHD), and obesity, respectively. The frequencies of T allele for -47833C>T and -98368G>T in Turkish adults were determined to be 0.35 and 0.33, respectively. -47833C>T was significantly associated with higher fasting glucose concentrations in all participants, especially in men. Both SNVs were significantly associated with diabetes and CHD in all participants (p<0.05). When study population was stratified according to sex, -98368G>T was associated with diabetes in women (p=0.041) and -47833C>T was associated with diabetes and CHD in men (p=0.018 and p=0.032, respectively). Also, both SNVs and the diplotypes of common haplotype (H1) remained strongly associated with type 2 diabetes after risk factors were adjusted (p<0.05). Conclusion: T allele homozygosity of two SNVs as well as the diplotype H1-/H1- reflects risk of diabetes primarily in men. Enhanced CHD risk is determined by the presence of diplotype H1-/H1- among nondiabetic participants.